Case reportDermatitis artefacta as a symptom of schizophrenia? - Kępska, Anna; Majtyka, Magdalena; Kowman, Maciej; Kłoszewska, Iwona; Kwiecińska, Ewa; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Dermatitis artefacta is a disease that occurs as a result of a self-inflicted injury of the skin. The skin lesions are most often located on the areas within easy reach of the patient’s dominant hand sparing the middle part of the back. Dermatitis artefacta may coexist with psychiatric disorders and imitate many dermatologic diseases. As most of the patients with self-inflicted dermatoses usually initially deny any psychiatric problems, what delays psychiatric intervention, they are typically first seen by dermatologists. We are reporting a case of a 35-year-old man with a 3-year-long history of schizophrenia who has been treated at a dermatologist’s office sequentially with acne, bacterial lesions, suspected tuberculosis. However, the treatment was ineffective. He was diagnosed with dermatitis artefacta after 7 years of disease duration. During this time he was treated with many medicines e.g. isotretinoin, which is contraindicated in psychosis as it worsens the course of disease. After establishing the correct diagnosis and antipsychotic treatment, a significant improvement was obtained in both skin condition and mental state. These are the reasons why we would like to recommend close cooperation between dermatologists and psychiatrists.